A gestão de ações de responsabilidade social empresarial e a interface com o Serviço Social - Aguiar, Tassiany Maressa Santos (2017)
The presented master's degree dissertation has a research objective- Management of corporate social responsibility actions, at companies that count on the presence of social workers, in the state of São Paulo. Our overall objective was to investigate and analyze the processes of managing social enterprise responsibility actions along with social workers. Therefore we divided the study in three important chapters of theoretical discussion and one field research. In the first one we discuss the corporate social responsibility as a form of management that is defined by an ethical and transparent relationship of the company with all public it is related with. Integrating an expanded sense of sustainability and its interlocution to Ethos institute of social responsibility. In the second chapter we discuss the management in scope of corporate social responsibility and the important process of evaluate the actions. Third chapter is dedicated to social work and its interface in the process of management and evaluation of social corporate responsibility. Finally, in the fourth part we present the field research in which we collected information about the companies linked to Ethos institute, subject of this research, located in state of São Paulo, which was with or without social worker's presence. Highlighting facing of present challenges among this socio occupational space and possibilities for social service work corroborated to the professional ethical political project principles. In this context we introduce a qualitative analysis through a critical reading of reality, using the methodology based on the dialectic method that shows possible correlation between theory and practice